A Prediction Model Incorporating Peripheral Eosinopenia as a Novel Risk Factor for Death After Hospitalization for Clostridioides difficile Infection - Ying Wang; Hojjat Salmasian; Aaron Schluger; Angela Gomez-Simmonds; Alexa Choy; Jianhua Li; Jordan E. Axelrad; Daniel E. Freedberg (Gastro Hep Advances, 2022)
Background and Aims: Clostridioides difficile infection (CDI) is associated with a range of outcomes, and existing prediction models for death among patients with CDI are imprecise. Peripheral eosinopenia has been proposed as a novel risk factor for death among patients with CDI but has not been incorporated into prediction models. This study aimed to develop and validate a prediction model for death among patients hospitalized with CDI that incorporated peripheral eosinopenia. Methods: Eosinopenia was defined as 0 eosinophils/μL on the soonest peripheral blood drawn within the 48-hour window of the CDI test (before or after). Adults were eligible for the study if they were hospitalized at any one of 3 large, unaffiliated hospital networks, tested positive for CDI by stool polymerase chain reaction, and received appropriate anti-CDI treatment. Patients were followed for all-cause death for up to 30 days. Results: There were 4518 unique hospitalized adults with CDI included (2142 in the derivation cohort and 2376 in the validation cohort). All-cause 30-day mortality was 9% and 10% in the cohorts. In the validation cohort, the factors most strongly associated with death were eosinopenia (adjusted odds ratio [aOR] 2.49, 95% confidence interval [CI] 1.77–3.50), albumin <3 g/dL (aOR 3.26, 95% CI 2.13–3.49), and creatinine >1.5 mg/dL (aOR 2.55, 95% CI 1.86–3.49). A 6-variable clinical prediction model was developed that improved on existing classification schemes for CDI severity (area under the receiver operating characteristic curve of 0.75 vs 0.68). Conclusion: Among adults hospitalized with CDI, peripheral eosinopenia was associated with increased risk of all-cause 30-day mortality. A prediction model incorporating peripheral eosinopenia was developed to improve care for hospitalized patients with CDI through risk stratification.